Green synthesis and antifungal mechanism of silver nanoparticles derived from chitin‐ induced exometabolites of Trichoderma interfusant. (23rd December 2019) - Hirpara, Darshna G.; Gajera, H.P.
Abstract : The potent biocontrol agent Trichoderma interfusant (Fu21) derived by protoplast fusion of mycoparasitic T.virens NBAII Tvs12 and multistress (fungicides and abiotic stress) tolerant T. koningii MTCC796. The chitin‐induced exometabolites harvested by culturing the diverse and stress tolerant Trichoderma fusant (Fu21) and utilized for synthesis of green silver nanoparticles (Ag‐NPs). Green Ag‐NPs characterized for size (62.6 nm in PSA), shape (spherical with 59.66 ± 4.18 nm under SEM), stability (51.2 mv as ZETA) and purity (3.40 ke V peak corresponded to the binding energy of silver under EDAX). A Fourier transform infrared spectroscopy exhibited electromagnetic spectra of various functional groups of exometabolites conforming the synthesis of green Ag‐NPs. We investigated novel route and mechanism of mycelial degradation at minimum inhibitory concentration (MIC) of green nanoformulation (20 μg Ag.ml −1 ) to restrain phytopathogen Sclerotium rolfsii. The antifungal action of green Ag‐NPs on MIC at 3 DAI elevated the mycelial cell membrane leakages (sugars and proteins), lipid peroxidation, depressed the respiratory chain dehydrogenase activity and destroyed the structure of S. rolfsii mycelia (SEM morphology) which cause phytopathogen to die. The use of green Ag‐NPs as antifungal agent is considered to be eco‐friendly resource, alternate to fungicides and cost‐effective means to diminish phytopathogen S. rolfsii causing stem rot in groundnut. Further, bioefficacy of green Ag‐NPs against S. rolfsii may be tested under field condition in groundnut rhizosphere which proved sustainability and it's advancement towards greener chemistry. Abstract : The study critically assessed green Ag‐NPs, derived from exometabolites of Trichoderma interfusant, for particle size distribution, morphology, stability, purity and functional group of exometabolites utilized in Ag‐NPs synthesis (FT‐IR). A novel route of antifungal mechanism of green Ag‐NPs examined that have been considered as fungicides alternate, cost‐effective and eco‐friendly management strategy to control phytopathogen. The study explained bio‐controller based green nano‐product as a potential template to design novel antifungal agent and overcome the issue of infection in plant fungal diseases.